2007
DOI: 10.1002/micr.20443
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation and neurogenesis of neural stem cells enhanced by cerebral microvascular endothelial cells

Abstract: In adult mammalian brain, vascular cells reside throughout life, close to central nervous system germinal zones, and neural stem cells (NSCs) mainly localize in the dentate gyrus of the hippocampus, subventricular zone, and olfactory bulb. Microvessels appear to produce a special microenvironment that may influence the characteristics of NSCs. To explore this potential correlation, an in vitro model with cocultured cerebral microvascular endothelial cells (CMECs) and NSCs was established in our study by using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…The wells were viewed regularly under an inverted microscope (Olympus, Japan). Our observations confirmed that the CEC plated in the upper compartment were unable to migrate through the membrane pores into the space containing the BEPC, whereas the secreted cytokines were free to move [Guo et al, 2008]. After 10 days of coculture, transmission electron microscopy (TEM) and scanning electron microscopy (SEM) were also used to examine the shape and presence of tight junctions in the induced BEPC.…”
Section: Coculture Of Bepc and Cecsupporting
confidence: 56%
“…The wells were viewed regularly under an inverted microscope (Olympus, Japan). Our observations confirmed that the CEC plated in the upper compartment were unable to migrate through the membrane pores into the space containing the BEPC, whereas the secreted cytokines were free to move [Guo et al, 2008]. After 10 days of coculture, transmission electron microscopy (TEM) and scanning electron microscopy (SEM) were also used to examine the shape and presence of tight junctions in the induced BEPC.…”
Section: Coculture Of Bepc and Cecsupporting
confidence: 56%
“…1) An important mechanism seems to be the expression of neurotrophic factors [28]. 2) Progenitor cells are capable to enhance endogenous neurogenesis of neural stem cells in the CNS via angiogenesis [29][30][31]. 3) In addition, in vitro studies have demonstrated the ability of HSCs to transdifferentiate into neuron-like cells [12,32].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the majority of molecules shown to be essential for dentate gyrus development are most well known for neurogenesis that occurs during early brain development (Doetsch, 2003;Guo et al, 2008;Riquelme et al, 2008;Zhao et al, 2008). Molecules specific to neurogenesis within the more mature dentate gyrus remain elusive.…”
Section: Introductionmentioning
confidence: 99%